EXISTENCE OF MORAL CHARACTER IN THE PLAY JENAR BABAD TANAH PENGGING (Used Review of Content Analysis) - Muhamad Muhamad Ichsan Nurjam’an; Yumna Rasyid; Miftahulkhairah Anwar (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2018)
AbstractThis study aims to reveal the types of moral existence of the main character Syekh Siti Jenar, the disclosure and description of the moral of Sheikh Siti Jenar, and the moral of Sheikh Siti Jenar with the reality of life in the Laker Babad Tanah Pengging by Saini K.M. The study was conducted form October 2016 to August 2017. This research uses descriptive qualitative method with content analysis technique starting focus of research, data collection, verification of data validity, analyze, interpret, find, verify, and conclude. The results show that this play contains a positive moral existence that can be used as a reference to study literature. The content of the play is closely related to the life of the community so the result of the research is suggested that the play "Syekh Siti Jenar in Babad Tanah Pengging," by Saini K.M. can serve as a medium for teaching individual, social, and moral religious which concerned about the moral issues of the students that occur in the process of literary learning.Keywords: The play, Main Figures, and existence of Moral